2002
DOI: 10.1074/jbc.m207426200
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of CDK5 Activator p35 Induces Intensive Phosphorylation of Ser202/Thr205 of Human Tau

Abstract: Hyperphosphorylated tau is a major component of neurofibrillary tangles, one of the hallmarks of Alzheimer's disease. CDK5 is a kinase that phosphorylates the tau protein, and its endogenous activator, p35, regulates its activity. Recently, calpain was found to digest p35 to its truncated product, p25. Several lines of evidence suggest that p25-CDK5 has much more powerful kinase activity and that it may cause abnormal hyperphosphorylation of tau. In this study, we have examined the kinetic characteristics of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 25 publications
2
100
1
Order By: Relevance
“…In contrast to the results of Hashiguchi et al (26), we find that the kinetic parameters of both enzymes for the phosphorylation of these substrates are the same within experimental error. In addition, we have examined the phosphorylation of individual target sites in tau by two-dimensional NMR.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast to the results of Hashiguchi et al (26), we find that the kinetic parameters of both enzymes for the phosphorylation of these substrates are the same within experimental error. In addition, we have examined the phosphorylation of individual target sites in tau by two-dimensional NMR.…”
contrasting
confidence: 56%
“…To rigorously demonstrate its hyperactivity, however, it is necessary to show that the catalytic parameters associated with steady-state phosphorylation of substrates are different between the two enzymes. Hashiguchi et al (26) previously conducted such experiments, and concluded that the intrinsic activity of CDK5/p25 was indeed significantly higher than that of CDK5/p35. Their data, however, consisted of few data points and was fraught with large errors.…”
mentioning
confidence: 99%
“…The association between Cdk5 activation and cell death is seen in pathology: rat lungs infected with Streptococcus pneumoniae, 25 mouse limbs infected with Leishmania major, 26 preterm lamb lungs after ventilation, 27 cyclophosphamide-treated mouse embryos, 28 and several neurodisorders and neuronal injuries. [29][30][31][32][33][34][35][36][37] The regulatory signals and mechanisms by which Cdk5 is activated remain undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of these data yielded a Km of 4 µM for tau and 35 µM for ATP, which are similar to the reported values. 36 The recovery of this filter assay was determined to be 36% by using 125 Iprotein. Different concentrations of tau were then incubated with the kinase, and the reaction was terminated with EDTA.…”
Section: Substrate-dependent Phosphorylationmentioning
confidence: 99%